Determination of tooth surface points on bevel gears for checking on a coordinate measuring machine - Várkuli, Miklós; Bognár, Gabriella; Szente, József (Design of Machines and Structures, 2023)
The use of coordinate measuring machines is an integral part of gear design. In order to this tool to be truly effective, it is necessary to know the surfaces to be measured and to provide comparative values. In the study, the mathematical modelling of the bevel gear tooth surfaces and the exact description of the production are used to produce the theoretical surfaces on which points can be added in any desired arrangement and number. These points form the basis for the evaluation of the measurement by comparison with the measured values.